If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -6.2 = 14.2 Reorder the terms: -6.2 + 3x = 14.2 Solving -6.2 + 3x = 14.2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6.2' to each side of the equation. -6.2 + 6.2 + 3x = 14.2 + 6.2 Combine like terms: -6.2 + 6.2 = 0.0 0.0 + 3x = 14.2 + 6.2 3x = 14.2 + 6.2 Combine like terms: 14.2 + 6.2 = 20.4 3x = 20.4 Divide each side by '3'. x = 6.8 Simplifying x = 6.8
| -8d=-9d+7 | | 30=-5/2u | | 90=(x+2)(y+1.5) | | 7f/3=5 | | m^2-10m+19=-8 | | 5X+3-X=15+X | | 4c=(a-b)/3 | | 49v^2+16=-56v | | b/3=15.2 | | 10n=7n+9 | | log(132-4x)=2 | | 54=d | | 2x+54=24 | | Cos(5x)=0.8 | | 1200m=600 | | -10+c=-4c | | -(8y-3)-(-7y-8)=9 | | 6n=43 | | 1-2n=-10+5-n+4n | | -5+2a-8a=42 | | 3y+21=6y | | 2+3x=5(x-3) | | -3p(p+2)=-30 | | 7e^5x=924 | | -2n+2=-3n-5 | | 11x-3x+90=11x+36 | | a-5+2a-8a=42 | | 8h=168 | | x/10-4=4 | | 7a-11=38 | | 8(-4a-1)=3(10a) | | -11+5x-7+5=3+6x+x |